Balance training improves memory and spatial cognition in healthy adults. Issue 1 (December 2017) - Rogge, Ann-Kathrin; Röder, Brigitte; Zech, Astrid; Nagel, Volker; Hollander, Karsten; Braumann, Klaus-Michael; Hötting, Kirsten
Abstract Physical exercise has been shown to improve cognitive functions. However, it is still unknown which type of exercise affects cognition. In the present study, we tested the hypothesis that a demanding balance training program improves memory and spatial cognition. Forty healthy participants aged 19–65 years were randomly assigned to either a balance or relaxation training intervention. Each group exercised twice a week for a total of 12 weeks. Pre- and posttests assessed balance performance, cardiorespiratory fitness, memory, spatial cognition, and executive functions. Only the balance group significantly increased in balance performance from pre- to posttest, while cardiorespiratory fitness remained unchanged in both groups. Moreover, the balance group significantly improved in memory and spatial cognition. Effects on executive functions were not observed. These results suggest that balance training is capable of improving particularly memory and spatial cognition. Therefore, an increase in cardiorespiratory fitness does not seem to be necessary to induce beneficial effects of physical exercise on cognition. It might be speculated that stimulating the vestibular system during balance training induces changes of the hippocampus and parietal cortex possibly via direct pathways between the vestibular system and these brain regions.